Fungsi Badan Pertanahan Dalam Pendaftaran Hak Milik Atas Tanah di Kabupaten Sikka - Adriana Rosalindra Kondi; Saryono Yohanes; Yoh G. Tuba Helan (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The human need for land from day to day continues to increase, in line with the rapid development in all fields carried out. This is the basis for the importance of registering land with the National Land Agency. Which is the formulation of the problem (What is the function of the land agency in realizing the land registration program in Sikka Regency? (2) What are the inhibiting factors faced by the Land Agency in the implementation of complete systematic land registration in Sikka Regency?. The methods in this study are (1) Normative research, namely research whose data is taken from laws and regulations, (2) Empirical research, namely how the law works in society. The results of the study show that the Land Agency has an important role in ensuring legal certainty over land ownership through a systematic registration process. The function obtained by the Sikka Regency Land Office is to carry out the determination of land ownership and land registration based on the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency Number 17 of 2020 concerning the Organization and Work Procedures of the Regional Office of the National Land Agency and the Land Office. However, there are several obstacles faced, including lack of human resources, unclear land ownership status, expensive registration fees, lack of public understanding. The author's conclusions: (1) The National Land Agency in realizing PTSL in Sikka Regency has carried out its function in determining land rights and land registration in accordance with the MINISTERIAL REGULATION ATR/BPN No. 17 of 2020. (2) Inhibiting factors include the lack of human resources in the Sikka Regency Land Office, the implementation of measurements of many people who put up land boundary signs that are not massive, and the lack of community mindset towards the importance of taking care of the issuance of land certificates. The suggestions: (1) For the Sikka Regency Land Office, it is hoped that complete systematic land registration activities in Sikka Regency are carried out in accordance with applicable regulations and determined targets so that legal certainty and land ownership can be realized properly. (2) For the National Land Agency of Sikka Regency, Sikka Regency should often conduct socialization regarding the management of land certificates and also coordinate with the local government.